On the use of opportunistic vehicular communication for roadside services advertisement and discovery - Ullah, Kifayat (2016)
Vehicular Ad hoc Network (VANET) is a special kind of Mobile Ad hoc Network (MANET) and is a key enabling technology for Intelligent Transportation Systems (ITS). It plays an important role in the deployment of a large scale of both safety and non-safety applications. Among non-safety applications, an important and challenging area is the provision of information about roadside services advertisement and discovery. In this work, we adopted the beaconing strategy and opportunistic vehicular communications to address the problem of roadside services advertisement and discovery on the highways. Our approach offers several advantages over the traditional billboard method, e.g., low cost, targeting a large number of customers in a real time, more control over the advertisement campaign, dynamic content updating, and discovery of services far ahead of the business region. For advertising roadside services, we followed the push-based advertisement strategy and relied on Infrastructure-to-Vehicle (I2V) communications only. On the other hand, for discovering these services by the drivers, we used pull-based advertisement strategy and opportunistic Vehicle-to-Vehicle (V2V) communications. In order to contribute to the advertisement campaign, we used the store-carry-and-response mechanism. Our first contribution is the Extended Opportunistic Service Discovery Protocol (EOSDP). EOSDP implements and extends the original version of Opportunistic Service Discovery Protocol (OSDP) via simulation experiments. We used Simulation of Urban Mobility (SUMO), Objective Modular Network Testbed in C++ (OMNET++), and Vehicles in network simulation (Veins) simulators. Our second contribution is Service Advertisement Protocol (SADP). SADP is a lightweight beaconing-based services advertisement protocol for VANETs. It does not require the Internet connection for advertising the roadside services. Moreover, SADP modeling is based on VANETs standard protocols. The performance of SADP was evaluated in a congested highway scenario with varying speed of vehicles and under different broadcast frequencies. Our last contribution is Commercial Services Discovery Protocol (CSDP). Like the previous protocol, CSDP is a lightweight beaconing-based services discovery protocol for VANETs. CSDP is infrastructureless protocol which only depends on opportunistic V2V communications for roadside services discovery. The protocol was implemented in congested highway scenario and extensive set of simulation experiments were performed to evaluate its performance under different parameters, e.g., Query Interval (QI), Query Attempts (QA), and Time to Live (TTL).